THE MEANING AND SYMBOLISM OF SURAH AL-LAHAB FROM THE PERSPECTIVE OF ROLAND BARTHES' SEMIOTICS - MZ, Isniyatun Nizwah; Rohmatika, Arina; Hidayah, Nurul (Journal of Arabic Language and Literature (ALLAIS), 2024)
The data for this study were sourced directly from the Qur'anic text of Surah al-Lahab, complemented by interpretations from classical and contemporary Tafsir literature, including Tafsir Ibn Kathir and Tafsir al-Misbah. Data were collected through textual analysis, identifying key terms such as لهب (lahab), يدا (yadaa), سيصلى (sayaslaa), الحطب (al-hatab), and مسد (masad), which serve as signifiers. These were then analyzed using semiotic techniques to reveal their denotative meanings ("flame," "both hands," "firewood," and "fiber rope") and connotative interpretations that symbolize punishment, loss, and eternal suffering. The study employed a qualitative approach, integrating linguistic and semiotic analysis to uncover layered meanings in the text. Roland Barthes' semiotic framework was utilized to deconstruct the mythological and ideological dimensions of the Surah. Findings indicate that Abu Lahab (real name: Abdul-Uzza) epitomizes loss and condemnation to Hellfire for his hostility toward the Prophet Muhammad (peace be upon him). Furthermore, his wife, complicit in spreading slander and opposing the prophetic message, faces similar punishment as described in the Surah. This research underscores the symbolic and ideological richness embedded in the Qur'anic narrative.